2020
DOI: 10.5435/jaaosglobal-d-20-00151
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Social Media Posts and Academic Citations of Orthopaedic Research

Abstract: Introduction: The objectives of this study were to quantify adoption of social media for the dissemination of original research in orthopaedic research and to determine the correlation between academic citations and social medial posts among recent orthopaedic publications. Methods: An Internet-based study was performed of 835 articles from three orthopaedic journals from 2018 to 2019. The number of academic citations for each article was determined using Google Scholar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 15 publications
(26 reference statements)
2
45
1
1
Order By: Relevance
“…A recent article similarly demonstrated that the Altmetric score of a publication demonstrated a significant, but weak positive correlation with the citation rate within orthopedic literature [ 12 ]. Similarly, Zhang and Earp describe the positive relationship between social media posts and academic citations in recent orthopedic research [ 13 ]. This suggests that the Altmetric score could potentially resemble a quantifiable assessment of the publication’s impact and its ability to garner attention within the scientific community [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent article similarly demonstrated that the Altmetric score of a publication demonstrated a significant, but weak positive correlation with the citation rate within orthopedic literature [ 12 ]. Similarly, Zhang and Earp describe the positive relationship between social media posts and academic citations in recent orthopedic research [ 13 ]. This suggests that the Altmetric score could potentially resemble a quantifiable assessment of the publication’s impact and its ability to garner attention within the scientific community [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of physicians using social media for professional purposes has reached upwards of 90%, allowing for sharing and dissemination of scientific literature [ 12 , 14 ]. In addition, many academic journals have adopted social media profiles to help share and distribute publications, contributing the ever-growing presence of social media in scientific literature [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature reviews may also be influenced by other arbitrary factors. For example, an author's social media presence showed a positive correlation with the rate at which they were cited [ 22 , 23 ]. Another consideration for citation rate is the primacy effect, which describes how citations listed earlier in a study are used more frequently than those that appear toward the end of a study [ 24 ].…”
Section: What Are the Root Causes Of Citation Inaccuracies?mentioning
confidence: 99%
“…Solutions to many of these problems have been shared [ [15] , [16] , [17] , 22 , 23 ]. Authors can help others find their research by using targeted rather than generic keywords [ 17 ].…”
Section: What Can Be Done To Prevent or Correct Citation Inaccuracies?mentioning
confidence: 99%